PENGARUH PROMOSI DAN EKUITAS MEREK TERHADAP LOYALITAS KONSUMEN CIPAGANTI TRAVEL - Soraya, Iin (Jurnal Komunikasi, 2015)
Customer loyalty can be said to be realized from the consumers know the product, the value of a product, the image of a product, a strong relationship from the consumer to the product by providing promotional and customer satisfaction with a product. Cipaganti Shuttle is a passenger service travel. Type of research is descriptive quantitative. Population rearch are consumer Cipaganti Travel branch BTC which amount to 235 person for day. Technique pulling sample applying for formula Solvin method, until sample commonly use amount to 70 respondent. Testing hypotheses using simple regression analysis linear, multiple regression analysis linear, Test f and t test is to determine. The result for Test f there is (1) a the promotion positive effect and significant on customer loyalty (2) a the brand equity positive effect and significant on customer loyalty (3) a the promotion and brand equity simultaneously have high significant positive effect on customer loyalty. Keywords: Promotion, Brand Equity, Consumer Loyalty, Cipaganti Travel.